2022
DOI: 10.1111/joss.12748
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 contamination through food: A study with Brazilian consumers of different socioeconomic and demographic characteristics

Abstract: This study aimed to investigate through free word association the perception of Brazilian consumers regarding the possibility of infection with the SARS‐CoV‐2 virus through food. One thousand individuals answered the questionnaire via an online platform. Most cited terms (hygiene—8%, fear—8%, caution—5%) and categories (negative attitudes and feeling—72% and sanitization—60%) were related to overall COVID‐19 infection rather than their specific infection through the food. The perception of the possibility of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…The adoption of these "new" habits and behaviors may have been directly influenced by the measures disseminated by the media and social networks and supported by medical authorities, especially those related to hand washing, the use of hand sanitizer (e.g., washing and disinfecting hands before and after handling purchases) and disinfection of surfaces and the packaging of purchased products (e.g., cleaning and disinfecting packaging with soap and water, using a damp cloth and bleach diluted in water and/or 70% alcohol to destroy the outer membrane of the virus and prevent infection) [89,[97][98][99][100][101][102][103][104]. These changes may also have been supported by the fact that SARS-CoV-2 was found in frozen foods and on their packaging [14][15][16][17][18]105], which may have been reflected in an increase in the consumption of home-produced foods to reduce handling, and thus the risk of contamination [54,55,[58][59][60][61][62][63][64].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adoption of these "new" habits and behaviors may have been directly influenced by the measures disseminated by the media and social networks and supported by medical authorities, especially those related to hand washing, the use of hand sanitizer (e.g., washing and disinfecting hands before and after handling purchases) and disinfection of surfaces and the packaging of purchased products (e.g., cleaning and disinfecting packaging with soap and water, using a damp cloth and bleach diluted in water and/or 70% alcohol to destroy the outer membrane of the virus and prevent infection) [89,[97][98][99][100][101][102][103][104]. These changes may also have been supported by the fact that SARS-CoV-2 was found in frozen foods and on their packaging [14][15][16][17][18]105], which may have been reflected in an increase in the consumption of home-produced foods to reduce handling, and thus the risk of contamination [54,55,[58][59][60][61][62][63][64].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies in some countries in Asia, Europe and the Americas have shown a change in behavior of the population regarding what to eat, what to avoid and how to prepare food, as well as an increase in concerns and doubts regarding COVID-19 and food safety [51][52][53][54][55][56][57][58][59][60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the emergence of the COVID-19 pandemic, numerous measures to control this virus's spreading have been taken worldwide 1 . Although several countries are vaccinating their population, the pandemic is not over yet 2 , and the treatment of COVID-19 is still a real challenge 3 – 5 , mainly due to the new emerging variants.…”
Section: Introductionmentioning
confidence: 99%